FAKTOR-FAKTOR YANG BERKAITAN DENGAN PRESTASI BELAJAR MAHASISWA - Hasminidiarty Hasminidiarty (Universitas Batanghari Jambi, 2015)
In each success has always been characterized by hard work with a perseverance to keep trying. Many students who graduated from universities with the best value, but not a few students who have not obtained the results with the value of the plume.Academic achievement research aims to investigate the extent to which a student can obtain a proud achievement, so that the factors studied and tested in the study include: learning in which students everyday, both in college and outside of class hours, style live or their daily habits, motivational lectures, circumstances, environment, intellectual ability of each individual, the barriers of learning, student attitudes towards faculty and facilities provided by the college.In gathering the data used methods of questionnaires distributed to students of degree (S1) management of the Faculty of Economics, University of Batanghari from early June until the end of June 2015. In this questionnaire deploy taken a sampling of all students, including class of 2010 to 2013 that still forces active in the study program when the study was conducted using a stratified random method.Results of the research achievements of this study indicate that factors seating layout that is appropriate when studying in college, factor concentration skills of students while attending factor taking the average number of credits for each semester, utilization factor of library services, factor student attitude when getting Value C factor the main purpose of the lecture (seek and master of science), factor residency status of students, a factor learning barriers (difficulties getting along with friends on campus) and the factor of student satisfaction of all achievement results obtained during lectures proved the existence of a relationship of mutual dependence with the value student achievement to the extent of 5% of significance that it deserves the attention of students, especially for students to learn in college are still difficulties to reach this achievement and want to improve the results of learning in Higher EducationKey Word: factor residency status of students